2014
DOI: 10.22319/rmcp.v5i2.3662
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación del conocimiento de los ganaderos sobre la tuberculosis bovina e implicaciones para su control

Abstract: RESUMENDurante los meses de abril a julio de 2012, se entrevistaron a 154 ganaderos del norte de Portugal con el objetivo de evaluar su conocimiento sobre la tuberculosis bovina (TBb). De acuerdo con los resultados, 14.3 % de los ganaderos declararon haber tenido, al menos una vez, el hato infectado con TBb. Además, estos mostraron que los ganaderos poseen un buen conocimiento de la enfermedad a pesar de la elevada edad y de la baja escolaridad/formación. Sin embargo, los resultados mostraron que el 27.9 % de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…2010; Brennan and Christley 2013; Toma et al . 2013; García and Coelho 2014; Laanen et al . 2014; Sarrazin et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2010; Brennan and Christley 2013; Toma et al . 2013; García and Coelho 2014; Laanen et al . 2014; Sarrazin et al .…”
Section: Introductionmentioning
confidence: 99%
“…Dairy cattle farmers implement biosecurity practices in a heterogeneous manner that may not observe biosecurity standards, sometimes including little or no implementation (Brennan and Christley 2012;Sahlström et al 2014;Renault et al 2018b). There are considered to be various (favourable and unfavourable) internal and external factors that determine whether farmers implement biosecurity practices, such as: experience, knowledge, understanding, attitude, motivation, sources of information, economy, perception of the importance and effect of biosecurity, animal welfare, internal and external cohesion, obligatory and voluntary biosecurity, availability of time and space, farm size and facilities, climate and behaviour of other agents, among others (Nöremark et al 2010;Brennan and Christley 2013;Toma et al 2013;García and Coelho 2014;Laanen et al 2014;Sarrazin et al 2014;Toma et al 2015;Broughan et al 2016;Frössling and Nöremark 2016;Naylor et al 2016;Ciaravino et al 2017;Renault et al 2018c;Moya et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have identified several psychosocial factors in dairy farmers and veterinarians that might influence their decision on whether or not to implement biosecurity measures. Among these factors, it has been described that the attitude of farmers and veterinarians towards the implementation of biosecurity measures might be affected by the technical knowledge they have (Frössling & Nöremark, ; García & Coelho, ; Toma, Low, Vosough, Matthews, & Stott, ), the individual experiences they have lived (Broughan et al, ), the importance they can attribute to risks (Renault, Humblet, et al, ), and the benefits they can obtain from measures implemented (Ciaravino et al, ). Moreover, their behaviour towards the implementation of biosecurity measures has also been related to their perceived social pressure to apply these measures (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of biosecurity measures by farm stakeholders, such as farmers and veterinarians, can be influenced by individual, collective, local and general psychosocial factors. Individual factors include age and gender, whereby older farmers are stricter about the entry of animals of unknown health status and women have a higher level of education (3); information sources, for which purpose farmers can turn to veterinarians, magazines and media, other professionals, and the government (4,5); education and knowledge, whereby farmers and veterinarians with higher levels in this regard are more willing to promote biosecurity and to invest money and time in it (3,(6)(7)(8)(9); and risk-benefit perception, whereby more perceptive farmers and veterinarians prevent animals from interacting with others that are at risk of infectious disease, and less perceptive veterinarians in this regard do not consider themselves a risk, and do not organize their visits in consideration of the risk of a farm having an infectious disease (10-12). Collective factors include communication dynamics, whereby poor communication between veterinarians and farmers can negatively affect biosecurity (13,14); and interpersonal relationships, where a trusting relationship between veterinarians and farmers encourages collaboration to improve biosecurity (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%